Colour variation of Water Pipit Anthus spinoletta in winter plumage - Andersson, Reino (Ornis Svecica, 2024)
This study of colour variation on Water Pipit Anthus spinoletta in winter plumage, is based on photos of 93 individuals from southern Sweden. Using moulting criteria, the birds were aged from the photographs, and the presence or absence of five specific plumage characteristics were recorded. Twelve individuals in this study confirm the hypothesis that adult Water Pipits show a distinct combination of plumage traits during winter. However, the presence of these plumage traits varied in younger birds in their first winter plumage. Among the 81 individuals classified as first winter plumage, 23 (28%) displayed all “adult characteristics”, 32 (40%) one to four of the characteristics, while 26 (32%) lacked all “adult characteristics”. The latter group thus lacked a gray nape/crown, whitish supercilium, and lighter brown colouration of the mantle/scapulars. Ever since the first Swedish records in the mid-1990s, there have been ongoing discussions regarding species-specific characters in Water Pipits. The present quantification of colour variation in different age groups complements previous criteria for a reliable species identification of Water Pipits in winter plumage.